ANALISIS FAKTOR-FAKTOR PENGELOLAAN MANAJEMEN USAHA PETERNAKAN AYAM RAS PETELUR DI KABUPATEN 50 KOTA PROVINSI SUMATERA BARAT - Fenita, Yosi (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2011)
This research was conducted to address micro climate problem of tropical country such as Indonesia on layer production performance. Thise research is aimed to investigate determinant factors on productivity and technical aspects applied in layer farming of Lima puluh Kota District. Fourty Eight breeders were selected using simple random sampling based on their production scale. Cobb – duglass model was appliedto determine significant factors of productivity and Benefit Cost Ratio is applied to measure economic efficiency. Results showed that there were significant differences on rectal temperature (P<0.05), cage density (P<0.05) and protein intake (P<0.01). The layers farming scales were categorized into three groups; small scale (SI), medium scale (SII) and big scale (SIII). In addition, the strains reared by the farmers were Dekalb Warren, Super Harco, Lochmann did not significantly affect the layers performance. t-test results revealed that the farming scale did not have correlation (P>0.05) with the temperature of layer cages; which was 25.580C. The highest humidity level recorded was 80.54 measured in SI. The rectal temperatures were insignificant among scales; however, there were significant differences between Dekalb Warren and Lochmann (P<0.05). The highest rectal temperature was Lochmann. t-test results on cage density found that there was very insignificant between SII and SIII (P<0.01); which was 6.588 chicken/m2. Another parameter measured was protein intake, which was highly significantly differed among groups (P,0.01). The highest on SIII (19.42 g per chicken per day). In contrast, other parameters such as energy intake, age of laying period, feed in take, feed conversion, egg weight and egg shell thickness were insignificant among groups of farming scales as well as chicken strains (P>0.05). Economical analysis on the groups of layer farming scales showed that SI was different from SII (P<0.05); in addition, SI was highly significantly different from SIII, SII and SIII were insignificantly different (P<0.01). The higher the scale of the layer farming, the higher profits gained. Keywords: Layer productivity, determinant factors, economic efficiency